2015
DOI: 10.17352/2455-1759.000007
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Evidence Regarding the Quality of Life of Total Laryngectomees

Abstract: Introduction: The loss of laryngeal voice after total laryngectomy can have an impact on the quality of life and communication of affected individuals. Postoperative phonatory methods may promote advantages in oral communication and reduce the functional, organic and emotional changes experienced by the patients. On this basis, the objective of the present study was to review the literature in order to determine the impact on the quality of life of total laryngectomees according to the form of rehabilitation c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 42 publications
0
5
0
3
Order By: Relevance
“…In contrast, the esophageal voice is the most used in developing countries due to the low cost but has a lower success rate. Voice restoration with the tracheoesophageal prosthesis results in better satisfaction and self-confidence and minimizes the patient's social constraints, generating positive effects on quality of life, in addition to being more heavily used in developed countries 11 , 39 , 40 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the esophageal voice is the most used in developing countries due to the low cost but has a lower success rate. Voice restoration with the tracheoesophageal prosthesis results in better satisfaction and self-confidence and minimizes the patient's social constraints, generating positive effects on quality of life, in addition to being more heavily used in developed countries 11 , 39 , 40 .…”
Section: Discussionmentioning
confidence: 99%
“…A study comparing healthy people to people who underwent vocal rehabilitation with a prosthesis or esophageal speech identified a statistically significant difference in quality of life after their analysis of social function 11 . This study proposes that the tracheoesophageal prosthesis can be considered a gold standard for speech rehabilitation 11 , 16 , 34 , 39 . In addition, this study regards the esophageal voice as the second treatment option 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported an improvement in voice quality after alaryngeal rehabilitation. 6 Regular use of voice prosthesis is associated with improved voice intelligibility. 7 The situation in India is comparatively different due to various factors such as low socio-economic status, illiteracy, and low accessibility to health care.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, all patients should be evaluated in a multidisciplinary environment and should have a detailed treatment and rehabilitation plan based on the results of this evaluation. Moreover, the fact that smoking as the primary factor in larynx cancer etiology is also the primary factor for COPD and lung cancer etiology and the fact that about 25 % of the head-neck region cancers metastasize in the lungs result in frequent respiratory system pathologies in these cases [5,6]. The purpose of the present study was to examine the long term respiratory system pathologies that may develop in larynx cancer patients who have undergone total laryngectomy operation, determine the possible respiratory issues in laryngectomy patients before they develop and develop rehabilitation programs for those that are determined.…”
mentioning
confidence: 99%